THE EFFECT OF ORGANIZATIONAL CULTURE AND EMOTIONAL INTELLIGENCE ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL COMMITMENTS AS INTERVENING VARIABLES (STUDY ON ZISCO IN FOUR BRANCHES OF YATIM MANDIRI FOUNDATION, EAST JAVA) - Rini Hardiyani, Siti Komariyah & Raden Andi Sularso (International Journal of Research Science and Management, 2019)
This study aims to analyze the determinants for employee performance in Yatim Mandiri Foundation based on the three factors that influence the employee performance. Main purpose of this study is to examine whether each of those factors has effect on the employee’s performance or otherwise. Data is collected from 39 employees in four branches of Yatim Mandiri Foundation through the form of questionnaires with a Likert typed-scale. Path analysis is applied to find the effect of three factors to the employee performance. The results reveal that the value of validity model test is 74,5 percent, indicate that the employees’ performance is explained by organizational culture, emotional intelligence, and organizational commitment while the remaining 25,5 percent are linked with other factors. This study concludes that: 1) There is a significant effect between organizational culture to the organizational commitment, 2) There is a significant effect between emotional intelligence to the organizational commitment, 3) There is a significant effect between organizational culture to the employee performance, 4) There is a significant effect between emotional intelligence to the employee performance, 5) There is effect and significant between organizational commitment and employee performance.